Double orifice mitral valve in an asymptomatic adult with an unusual combination of congenital malformations: a case report - Proença, G (2004)
We report a case of an asymptomatic adult patient, with several congenital malformations including an infrequent variant of double orifice mitral valve, postductal aortic coarctation, bicuspid aortic valve and an aneurysm of the right Valsalva sinus. The loss of support of the right coronary cusp of the aortic valve caused major aortic regurgitation. With the exception of the mitral valve, which was left untouched because it was neither stenotic nor regurgitant, all the other abnormalities were successfully corrected, in a two-step surgical approach.